A national audit of Australian dental practice distribution: do all Australians get a fair deal?. (15th April 2013) - Tennant, Marc; Kruger, Estie
Abstract : Australia is the sixth biggest (by area) country in the world, having a total area of about 7.5 million km 2 (3 million square miles). This study located every dental practice in the country (private and public) and mapped these practices against population. The total population of Australia (21.5 million) is distributed across 8, 529 suburbs. On average about one‐third of the population from each State lives in suburbs without practices and 46% live in suburbs with one to five dentists. Of those living within the study frameset, 86.6% live within 5 km of a private practice and 84.4% live within 10 km of a government practice. Australia's dental practices are distributed in a very uneven fashion across its vast area. Three‐quarters of suburbs have no dental practice and over one‐third of the population live in these suburbs. This research clearly identified that in a vast and uneven socio‐geographically distributed country, service planning, if left to market forces, will end with a practice distribution that is fixed by economic drivers of scale and not that of disease burden. A more population health‐driven approach to future design and construction of government safety net services is needed to address these disparities.